Islamic Consumption Behavior In Realizing Family Welfare - Januari, Anas Tania; Rofiq, Aunur; Khusnudin, Khusnudin (Islamic Banking : Jurnal Pemikiran dan Pengembangan Perbankan Syariah, 2024)
Consumption in a country's economy, with higher levels of consumption causing increased economic activity and changes in a country's national income. The impact of consumption on household financial stability, with excessive spending relative to income causing personal financial problems. material and spiritual well-being in the household, is very important in balancing worldly and spiritual needs for overall well-being. This research is qualitative research with a normative approach. Obtaining secondary data in the form of data on welfare indicators which refer to the consumption behavior of Indonesian people obtained from the Central Statistics Agency in a certain period. This data is used as a reference in the importance of discussing consumption behavior, especially in the context of sharia. Meanwhile, the behavioral theory approach is used for the purposes of analyzing the goals of consumption behavior by adhering to Islamic principles to realize prioritized welfare among households. Research shows that consumption behavior in realizing the welfare of Muslim families can be seen from several indicators listed in data processed by the Central Statistics Agency. Consumption pattern indicators are influenced by income levels which reflect people's purchasing power and abilities. Meanwhile, other indicators can be seen from the quality of health and nutrition, education, housing and other social issues, such as a lifestyle that follows the times